Computation of Euler's critical buckling load for a rod with stepwise varying cross-section using analytical approach and the finite difference method (Proceedings of Faculty of Civil Engineering, 2025)
This paper presents the computation of Euler’s critical buckling load for rods with stepwise varying cross-section using both an analytical method and the finite difference method. A comparison of results shows that the numerical method yields slightly lower, conservative values. The results contribute to the analysis of buckling in geometrically complex elements and can be used to validate numerical models.
Keywords: critical load; buckling; stepwise varying cross-section; analytical method; finite difference method